“Cura gay é o meu caralho!”: a normalização da homossexualidade e a Resolução CFP 1/99 - Teixeira, Natália Beatriz Viana (2014)
In this research I review the discourses of legitimation of CFP Resolution No. 1/99 (Res 1/99), and I seek answer in part: how a discursive practice that made real this policy worked out among other practices discursive, legal and political order? To do this, I analyze discourses present in the relationship between favorable and contrary statements to their institution, from the texts (1) of the res itself. 1/99; (2) Public Civil Action 2011.51.01.018794-3 filed by Judicial Session of Rio de Janeiro – MPF; (3) the PDC 234/11; (4) the CFP institutional site of news about the res. 1/99; (5) Selection of news CFP contrary to the Resolution No. 1/99 on the internet; and (6) Images of street manifestations, cartoons and memes available on the internet related to the negative reactions to the PDC 234/11. We employ a search method inspired by Foucault's archeology and genealogy; and describe happenings previous to the Res 1/99, that support their emergency related to the emergence of homosexuality as a pathology and their displacement to normality. I analyze the co-dependence between state, science and profession mutually legitimate in modern societies; I point limits of Res 1/99 as a strategy of resistance before the heteronormative regime; and, finally, outline how the identity polarization between gays and evangelicals demarcates and reifies victimization strategies, homogenization and integration that characterize the present intensification of social tension and intolerance.